Dinâmica d’água em um vertissolo da Bacia do Rio São Francisco sob influência de sódio - Oliveira, Mayra Carolina de (2018)
The effects of the exchangeable sodium percentage and water quality on the hydraulic properties such as water retention, diffusivity and unsaturated hydraulic conductivity of a Vertisol were investigated. The treatments consisted of four values of exchangeable sodium percentages (ESP): Original soil with ESP 0.56%, 0.39% ESP, 1.33% ESP and 4,21% ESP, and two water sources with three replicates. The sources used were water from the São Francisco River and deionized water. In order to determine soil water characteristic curves (SWC), the samples were initially saturated in water and submitted to suction values equivalent to 2, 4, 6, 8 and 10 kPa, in Buchner funnels and 33, 60, 100, 500, 1,500 kPa in Richards extractor. In order to determine soil´s diffusivity and unsaturated hydraulic conductivity, the methodology proposed by Bruce and Klute (1956), which consists of horizontal infiltration tests, was used. Increases in ESP increased the values of natural clay content (clay dispersed in water - (CDW). Soils with structure modified by the presence of salts in the solution tend to store more water when submitted to the same levels of matrix potential using deionized water. With the empirical model proposed to adjust θ versus λ data, a minimum determination coefficient of 79% was found, being considered efficient. Soil water diffusivity and unsaturated hydraulic conductivity decreased with increasing ESP and increased significantly with soil moisture. The sources of water used did not changes soil properties values when compared to each other. The water movement in the unsaturated soil was affected by the ESP elevation possibly due to the expansion and dispersion effects of the clay fraction.